LEAGUE OF EX-INTERNED AND POLITICAL PRISONERS Inventory of documents - LEAGUE OF EX-INTERNED AND POLITICAL PRISONERS (ARCA, 2018)
Private documents of the League established in 1946 for members of the Ossewa-Brandwag who were interned during the Second World War - periodicals
COVERAGE 1982-1983; 3 File; 0,10 Metre.
Keywords: LEAGUE OF EX-INTERNED AND POLITICAL PRISONERS; Ossewa Brandwag